외래간호사의 업무 중요도와 수행도, 전문직 자아개념이 직무만족에 미치는 영향. - 김 여 정; 장 해 나; 권 정 희; 황 진 주 (Journal of Korean Academy of Nursing Administration, 2020)
Purpose: The purpose of this study was to identify factors influencing job satisfaction among ambulatory care nurses. Methods: Data were collected through a self-evaluation survey of 129 nurses in one tertiary hospital. Data were analyzed using paired t-test, independent t-test, one-way ANOVA, Importance-Performance Analysis, Pearson correlation coefficients, and multiple regression analysis. Results: The mean scores were: for importance, 3.18 out of 4, for performance, 2.24 out of 4, for professional self-concept, 2.92 out of 4, and for job satisfaction 2.77 out of 5. There were statistically significant positive correlations between professional self-concept and job satisfaction (r=.37, p<.001). Stepwise multiple regression analysis showed that satisfaction with professional self-concept, clinical career, and age explained 47.0% of the job satisfaction of ambulatory care nurses (F=37.51, p<.001). Satisfaction with professional self-concept, clinical career, and age were statistically significant predictors of job satisfaction. Conclusion: Findings indicate motivation programs according to clinical career would be useful to improve job satisfaction of ambulatory care nurses. Additionally, continuous education should be provided to strengthen the professional self-concept of nursing professionals in both undergraduate curricula and clinical fields.